Investigating the impact of variety of e-retail delivery service options on customer retention - Soheila Zarinjoy alvar; shahin raz; Ali Tavakolifar (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to investigate the impact of the variety of electronic retail delivery service options on customer retention. The current research is applicable in terms of purpose, a survey research in terms of the method of data collection, cross-sectional in terms of time, and causal-descriptive in terms of nature and method. The statistical population of the present study includes users of electronic retail delivery services in the field of clothing, which was considered 384 people using Morgan's table due to the infinite population. These numbers were selected based on the available random sampling method. The collection tool in this research included a questionnaire used to confirm its validity, face validity and Cronbach's alpha were used for its reliability. To analyze the obtained data, descriptive statistical methods and structural equations method were used in the inferential statistics section; and SPSS and PLS software were used to perform statistical operations. The results showed that there is a positive effect between the varieties of e-retail delivery service options on customer retention. To fit the overall model, the GoF criterion method was used; the obtained value was equal to 0.638, which indicates the appropriate fit of the model. Extended Abstract Introduction Today, extensive knowledge of electronic consumer behavior and delivery service demands has been developed based on scientific and operational insights from urban or broad and undifferentiated environments (Olsson et al, 2019). Furthermore, the current e-consumer culture in urban environments, especially in developed e-commerce markets, is strongly shaped by fast delivery, innovative delivery solutions, and a wide range of services (Buldeo Rai et al, 2021). Furthermore, delivery service differentiation has been identified as a key strategy in engineering e-commerce growth. As the market evolves, new retail set-up services have become a source of competitive advantage (Javed and Wu, 2020), and the delivery experience has been accepted as an important touch point of consumers' e-retail experience (Vakulenko et al, 2019). Research shows that not only market leaders such as Amazon, but now also small and medium-sized retailers have realized how much they rely on services related to online shopping (Sorkun, 2019). In such an environment, an increasing number of customers are equipped with a large amount of information, and have gained the power to accept more risk. They are prone to change their store based on the higher value they get elsewhere, so that customer switching has become common and a challenge for retailers. In this new retail paradigm, overall satisfaction with an online retail experience is directly influenced by the delivery experience (Vakulenko, 2018) and post-delivery service. Extensive knowledge of consumer behavioral and emotional responses in e-retail and immersive retail settings provides rich insights for retailers and related service providers to develop sustainable market strategies (Selin Atalay et al., 2017; Sun et al., 2020; Xu, 2020). Therefore, according to the issues raised, the present research seeks to answer this question: what effect does the variety of electronic retail delivery service options have on customer retention? Theoretical Framework Service delivery The way of service delivery in relation to the customer is one of the very important things that can strongly affect the level of satisfaction and loyalty of customers and the word of mouth advertising of the organization's and company's services. Therefore, it is very important to identify the factors that can somehow affect the quality of employees' services and somehow harm their service delivery with customers (Mokhtaran et al, 2012). Service organizations, including the Social Security Organization, in order to provide a high level of service quality and thereby create value and satisfaction for their customers, must plan for their services and ensure the successful implementation of their plans. Therefore, good planning and effective implementation of service delivery programs are one of the main factors of the service delivery system. In addition, this study and continuous improvement of service procedures helps to optimize the service delivery system and increases the service standards of the organization. In the relevant literature, a large number of field studies show that the effectiveness of the service delivery system has a positive and significant effect on the customer's perception of the quality of the services they receive. Similarly, many studies, through empirical research, have proven the positive effect of the service delivery system on service quality (Nouri Gholami & Aref, 2022) Customer retention The customer is the key to the success of any organization and any economic business activity; the credibility of a successful organization is based on the long-term relationships of that organization with customers. Believing and acting on the principles of customer orientation, gaining the satisfaction of new customers, and keeping old customers are considered to be the most important factors in the success of the organization. (Salaripour, 2021). Tolooee et al, (2023) investigated the presentation of the purchase intention model and customer experience on customer behavior in virtual networks. The effect of mindfulness and customer experience (respect for the customer, importance of time, banking operation research, customer value culture, modern technology, offering facilities, enjoyment, queuing system, environment coloring, and excellent location) was proved on the satisfaction, loyalty, and trust of customers. The results showed that the dimensions of purchase intention and customer experience through the effect on customer behavior, a better understanding of mindfulness, and experimental factors among banking systems can increase satisfaction, loyalty, and also trust among customers of Afogh Korosh store. Also, the research model of the research has a good fit. Mostardinha (2023) investigated the segmentation of package delivery services. This paper investigates the segmentation problem of a parcel delivery service that wants to assign an operational area to each of its teams: given the number of scheduled deliveries for each area, such that a balanced service exists between departments, covers contiguous areas, and takes into account limited capacities for teams. In addition to being relatively easy to model, existing optimization tools and software provide poor results when increasing the dimensionality of these types of problems with exceeding computational capacity. In this paper, an integer programming model, along with a heuristic to return a faster solution, was implemented to solve a segmentation problem in two different situations. The main advantage of the proposed strategy, compared to previous strategies, is its simplicity and easy implementation, and at the same time it reflects the optimal solution. Research methodology The current research is applicable in terms of purpose, a survey research in terms of the method of data collection, cross-sectional in terms of time, and causal-descriptive in terms of nature and method. The statistical population of the present study includes users of electronic retail delivery services in the field of clothing, which was considered 384 people using Morgan's table due to the infinite population. These numbers were selected based on the available random sampling method. The collection tool in this research included a questionnaire used to confirm its validity, face validity and Cronbach's alpha were used for its reliability. Research findings To analyze the obtained data, descriptive statistical methods and structural equations method were used in the inferential statistics section; and SPSS and PLS software were used to perform statistical operations. The results showed that there is a positive effect between the varieties of e-retail delivery service options on customer retention. To fit the overall model, the GoF criterion method was used; the obtained value was equal to 0.638, which indicates the appropriate fit of the model. Conclusion The current research was conducted with the aim of investigating the impact of the variety of electronic retail delivery service options on customer retention. The results of this research are in agreement with the results of Tolooee et al, (2023), Mostardinha (2023), Rezaei Dizgah (2023), Staki Organi & Jarireh (2022), Nouri Gholami & Aref (2022), Yeik (2022), Pillai et al, (2022), Kavanagh et al, (2022), Doguchaeva et al, (2022), Mirzaee Azandariani & Arya (2022), and Mousaviyan (2021). Tolooee et al, (2023) showed that the dimensions of purchase intention and customer experience through the effect on customer behavior, a better understanding of mindfulness, and experimental factors among banking systems can increase satisfaction, loyalty, and also trust among customers of Afogh Korosh store. Also, the research model of the research has a good fit. According to the results of the research, the following suggestions are presented:  The development of human resources and the system of hiring people in the units for sending goods to remote areas can determine the best method for each area.  Measuring the satisfaction of customers in every rural and urban sector and receiving their suggestions to improve the condition of sending goods can affect their satisfaction.